An Evaluation on the Architectural Formation, Conservation Problems and Reuse of Ayvalik Georgala (Yorgola) Inn - Bilgic, Melis; Erdem, Ayten (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2020)
Railway transportation developed rapidly within the borders of Europe and the Ottoman Empire with the Industrial Revolution, and it has affected the urban fabric and architecture of the settlements through which the train way pass. Georgala or Yorgola Inn, which is the main subject of this research, was built with a mosque and a barracks in Ayvalik on the possibility of constructing the Bandirma, Balikesir, Soma, Kasaba (Turgutlu) Railway line that was granted in 1873. Therefore it is possible to conclude that Georgala Inn, which is designed in a neoclassical style and a two-storey masonry structure with an inner courtyard surrounded by porticos, was probably built in the 1870s or just after. After the inn was used for a short period in its original accommodation function, it remained dysfunctional during the Great War era, and then it was adapted for different functions during the Republic Period. At the present, the building has been abandoned and partially lost its authenticity value, and it is planned to be reused through a proper conversion by the Municipality of Ayvalik. The purpose of the present study is to explain the steps of the preservation process of this special building, which started by preparing the Conservation Project. Within the scope of the study, the original architectural features of Georgala Inn and the changes it went through in the historica process were examined, the analytical survey was made, restitution proposals were prepared according to the documents obtained from the archive research, and the restoration project was proposed, including the appropriate new function determined for the building, along with intervention decisions. By this study; the authenticity values and conservation problems of Georgala Inn, which is not well known in the literature up to date, have been identified,and intervention methods have been proposed to preserve it with a new function. Georgala Inn was a complex example to deal with the history, layers, interventions, and additions, but it provides a very instructive process and experience to understand how to study inside and during the research practice outside of a cultural asset. The first part of the article gives information about the architectural and urban characteristics of the Ayvalik district. In the second part, the historical background, location, spatial organization, construction technique, and materials of the building are examined throughly. The Inn is shaped around a central inner courtyard surrounded by porticos and covered with a glass skylight supported by metal construction elements, which is thought to had been built in later periods as an addition. The street facade of the four-open-faced building is stone-coated in Neoclassical style and is one of the most characteristic facades in Ayvalik. The restitution or historical analysis process is the main theme of the third part of the apresent study. There was a lack of archival documents about the building to enable an understanding of the first construction period Given the circumstances, the study brings the importance of physical traces which can be found on the building itself into the light, as a complimentary way of conducting retrospective research on specific architecture when the archive records are insufficient. As a result of examination with the findings of analytic survey and restitution projects, the original condition, previous layers, and current additions have been successfully identified. Besides, the observation tower which does not exist today has been identified through the old photographs and has been included in the first construction period restitution study. The fourth section of the study revolves around how some of the Georgala Inn's initial features were lost over time, due to the building's positioning as an internal factor, and traffic density, long term natural causes, improper uses and repairs, abandonment as external causes After evaluating the analytical survey and restitution, it is proposed to reuse the building as a Cultural Centre in the restoration approach which is presented in the fifth part. During the adaptation to the new proposed function, the main approach is to preserve the original layout and spaces, thus improper addition walls will be removed and the new required spaces will be designed with divider walls made of easily demountable materials. The concept of preserving the building with the pre-existing additions has been adopted due to the reasons listed below; - The lack of historic records that based on first construction period of the building; - People of Ayvalik remembering the structure as a hospital': as it was previously used as a medical institution; - The thought that removing the additions can cause damage to the building. In line with the restoration approaches introduced as the principal framework, the restoration practise of this important building which bears the importance of being a historical document': has antiquity';authenticity and artistic as well as uniqueness'' ,group',' memory and use values, should be carried out meticulously by conservation experts.
Keywords: Ayvalik; conservation; inn; re-use; restitution; restoration; survey; Architecture